Rethink culture, tourism, and heritage from a critical vision. : The case of the Maya train (Ágora de Heterodoxias, 2022)
The following paper is necessary, as the possibility of a critical approach to the conventional view of heritage, culture and tourism will allow us to reassess policies, discourses and actions undertaken by various actors who extol the socioeconomic benefits of the use of cultural assets, which gave rise to patrimonialization and touristification processes that relegate authentic socio-cultural and economic economic benefits to the communities that possess them. The method used for the reflective analysis considers three phases: the theoretical foundation of criticism in tourism and culture; an approach to a reality that evidences critical reflection; and, the conceptual proposal around rethinking the relationship between tourism, heritage and culture. In this reflective analysis, the document discusses the real impacts behind the patrimonialization of cultural goods, the role of the State and the hegemonic actors that establish a way of conceiving culture as domination. In contrast to this vision, the value of this as a form that emancipates and not that constrains, this from the reflexive critical contribution of the philosophical assumptions of culture, tourism and heritage with regard to the dynamics and practice of the activity called heritage tourism.
Keywords: Tourism; patrimonialization; critical approach